Dynamics of Central and Peripheral Cardiovascular Indices While Performing Repetitive Dosed Exercise Test (Baltic Journal of Sport and Health Sciences, 2011)
Research background and hypothesis. Various physical loads require a different level of activation of various physiological systems and physiological mechanisms, which can highlight the synergetic interaction between central and peripheral mechanisms. Research  aim.  The  aim  of  this  study  of  this  study  was  to  identify  and  compare  the  central  and  peripheral reactions of cardiovascular system while performing repetitive dosed exercise test.Research methods. The participants in the study (15 persons in each of the four groups: non-athletes males; non-athletes females; well-trained endurance runners and well-trained sprinters) performed three Roufier exercise tests, i. e. 30 squats per 45 s with two minutes of rest between exercising. 12-leads ECG was registered and the heart rate (HR), the duration of interval JT were measured and analysed. Changes of oxygen saturation (StO 2 ) in m. vastus leteralis were measured by near-infrared spectroscopy.Research results. One time performance of the physical load may not reveal any central and peripheral synergic peculiarities as adaptation to physical loads in cumulative. For non-athletes the performance of repetitive Roufier tests every two minutes produced the fatigue summation effects which were typical of central and peripheral indices; for well-trained athletes we observed the stability of central reaction and fatigue effects in peripheral responses.Discussion and conclusions. A lot of cardiovascular indices may indicate the summation effects of fatigue while repeatedly performing a Roufier Test with two minutes of rest between exercising. The peripheral changes start first and they impact the central cardiovascular changes.Keywords: electrocardiogram, dosed exercise test, oxygen saturation